2018
DOI: 10.1111/jcmm.14081
|View full text |Cite
|
Sign up to set email alerts
|

CD83+CCR7+ NK cells induced by interleukin 18 by dendritic cells promote experimental autoimmune uveitis

Abstract: Natural killer (NK) cells have been reported to play a pathological role in autoimmune uveitis. However, the mechanisms regarding NK cells in uveitis and factors that affect NK‐cell activation in this condition remain unclear. Here, we report that the number of CD3 ‐ NK1.1 + CD83 + CCR7 + cells is increased in the inflamed eyes within a mouse model of experimental autoimmune uveitis (EAU), and these cells express elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 66 publications
1
11
0
Order By: Relevance
“…However, in our recurrent NIAU cohort, we also detected significantly increased plasma levels of IL-10 (an important inhibitor of the production of proinflammatory cytokines, such as IL-1β and IL-6). The cytokines that we detected in the plasma of the study participants was significantly increased in the recurrent NIAU patients in its inactive stage, and several of these cytokines mainly appear in relation to natural killer (NK) cells, such as IL-6, which plays an important role in NK cells activation, or IL-10, which can be released from activated NK cells, as previously reported [60,61]. Furthermore, it has been shown that CD4 and CD8 T cell surface molecules are essential for the recognition and activation of T cells by binding to their corresponding class II/class I major histocompatibility complex ligands on an antigen-presenting cell.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, in our recurrent NIAU cohort, we also detected significantly increased plasma levels of IL-10 (an important inhibitor of the production of proinflammatory cytokines, such as IL-1β and IL-6). The cytokines that we detected in the plasma of the study participants was significantly increased in the recurrent NIAU patients in its inactive stage, and several of these cytokines mainly appear in relation to natural killer (NK) cells, such as IL-6, which plays an important role in NK cells activation, or IL-10, which can be released from activated NK cells, as previously reported [60,61]. Furthermore, it has been shown that CD4 and CD8 T cell surface molecules are essential for the recognition and activation of T cells by binding to their corresponding class II/class I major histocompatibility complex ligands on an antigen-presenting cell.…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, it has been shown that CD4 and CD8 T cell surface molecules are essential for the recognition and activation of T cells by binding to their corresponding class II/class I major histocompatibility complex ligands on an antigen-presenting cell. In fact, CD4 and CD8 can increase the antigen-induced IL-2 formation through distinct mechanisms [ 60 , 61 , 62 , 63 ]. Additionally, CD4+ T cells can promote NK cells and macrophages via INFγ, to kill host cells in certain conditions.…”
Section: Discussionmentioning
confidence: 99%
“…NK cells are a central component of the innate immune system and play a critical role in regulating the adaptive immune response. Those cells are known to have an essential role in generating the inflammatory response during uveitis [ 33 , 34 ] and in AMD pathogenesis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…6- to 8-week-old C57BL/6 mice were anesthetized by intraperitoneal injection of pentobarbital sodium (80 mg/kg). EAU was induced by active immunization as previously described ( 17 ). Briefly, mice were immunized with 400 μg inter-photoreceptor retinoid-binding protein (IRBP)1-20 (5 mg/ml, GPTHLFQPSLVLDMAKVLLD, purchased from China Peptides) emulsified 1:1 in complete Freund’s adjuvant (Chondrex) with an additional 100 μl mycobacterium tuberculosis H37R (5 mg/ml, BD biosciences) at six locations (footpads (2×), tail base, posterior neck and bilateral flanks (2×)).…”
Section: Methodsmentioning
confidence: 99%